Madrasah Management Based on Total Quality Management in Developing Student Character - Kholid, Idham (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article discusses the management of madrasa education from a Total Quality Management perspective. The main problem raised is why Madrasah management based on Total Quality Management (TQM) has not been able to develop the character of students in Jambi province? This article comes from qualitative research at three madrasas in Jambi Province, including; Islamic Junior High School 6 Sarolangun in Sarolangun Regency, Islamic Junior High School 2 Batang Hari in Batang Hari Regency, Jambi Province, and Islamic Junior High School 5 in Jambi City. Data collection was carried out through observation, interviews and documentation. The research results show that TQM-based madrasa management in developing student character in Jambi Province is carried out based on the integration of resource management systems that do not meet standards. The factors that influence TQM-based madrasa management in developing student character in Jambi Province are budget, facilities and infrastructure. Meanwhile, the strategy for improving TQM-based madrasa management is to develop student character in Jambi Province by encouraging teachers to work professionally Artikel ini membahas pengelolaan pendidikan madrasah dengan perspektif Total Quality Management. Permasalahan utama yang diangkat adalah mengapa pengelolaan Madrasah berbasis Total Quality Manajemen (TQM) belum mampu dalam mengembangkan karakter Peserta didik di provinsi Jambi? Artikel ini berasal dari penelitian kualitatif pada tiga madrasah di Provinsi Jambi antara lain; Madrasah Tsanawiyah Negeri 6 Sarolangun di Kabupaten Sarolangun, Madrasah Tsanawiyah Negeri 2 Batang Hari di Kabupaten Batang Hari Provinsi Jambi, dan Madrasah Tsanawiyah Negeri 5 di Kota Jambi. Pengumpulan data dilakukan secara observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa pengelolaan madrasah berbasis TQM dalam mengembangkan karakter siswa di Provinsi Jambi dilakukan berdasarkan pengintegrasian sistem pengelolaan sumber daya yang belum sesuai standar. Adapun faktor yang mempengaruhi pengelolaan madrasah berbasis TQM dalam mengembangkan karakter siswa di Provinsi Jambi adalah anggaran, sarana dan prasarana. Sedangkan strategi peningkatan pengelolaan madrasah berbasis TQM dalam mengembangkan karakter siswa di Provinsi Jambi dengan mendorong guru untuk bekerja secara profesional.